The contribution of fine needle aspiration biopsy in the diagnosis of Mycobacterial Lymphadenopathy with particular reference to children - Wright, Colleen Anne (Stellenbosch : University of Stellenbosch, 2010)
Thesis (PhD (Pathology. Anatomical Pathology))--University of Stellenbosch, 2009.